Evaluation of investment and innovative development of Ukrainian economy:evolutional approach - Mazur, J.O. (Економіка промисловості, 2014)
Considered that industrial development in Ukraine depends on effective tax regulation. It manifests itself in the creation of conditions for sustainable economic growth based on investment and innovation, and the tax system that convenient for taxpayers. However, in modern conditions Ukraine occupies one of the last positions by GDP per capita PPP. There are reduced total investments in the economy, the share of the costs of implementing the scientific and technological work in the total GDP etc. Evolutionary economics as scientific approach in the modern economic thought is considered for investigative of socio-economic processes and phenomena and based on long-term changes and changes in the behavior of agents, who take certain decisions. Such decisions don`t always lead to an increase in public (or private) welfare. The need to consider the patterns of change of rules and norms of the individual's behavior in space and time in terms of their evolutionary development is identified. This methodology may be useful from the standpoint of research tools of tax policy to stimulate investment and innovation activities of industrial enterprises in Ukraine. However, the use of the evolutionary approach for the analysis of tax instruments in the promotion of investment and innovation has not received sufficient development. For evaluation of investment and innovative development of the industry is proposed to investigate the socio-economic system, which consists of the components of the innovation economy, that interacting through causal relationships: government (tax and budget sectors), economic agents and households. Innovation generated from knowledge. Knowledge as innovation is transmitted to innovative enterprises. Since not all knowledge can be transformed into innovation, then there is their forgetfulness. All agents are equal bearers of knowledge, and all kinds of knowledge are equivalent. The result of functioning of components of the innovation economy is a quantitative assessment offactors of economic growth that determine its rate in terms of agents’ behavior change in the socio-economic environment. Evolutionary characteristics of agents' behavior are selection, variability, heredity. They have an impact on the each component’s behavior in the socio-economic environment. Thus the economy is growing (or evolves) in a fast changing environment. Proposed approach is used for evaluation of investment and innovative development of economy in the real socio-economic conditions in Ukraine. Substantiated, that public income is not enough for financing of spheres of production and human capital. Therefore, there is development of national economy with low rate. It eliminates the possibility of using of modern innovative technologies actually. The directions of tax policy to stimulate of investment and innovative development of Ukrainian economy are proposed. Проведено аналіз залежності інвестиційно-інноваційного розвитку промисловості від ефективної податкової політики в розвинених країнах і країнах БРІКС. Обґрунтовано доцільність дослідження податкового стимулювання інвестиційно-інноваційного розвитку промислових підприємств з позицій еволюційного підходу з урахуванням закономірностей зміни правил і норм поведінки господарюючих суб'єктів у просторі та часі на довгострокових інтервалах часу. Удосконалено еволюційну агентно-орієнтовану модель інвестиційно-інноваційного розвитку економіки для опису інерційного сценарію діяльності промислових підприємств України. Проведен анализ зависимости инвестиционно-инновационного развития промышленности от эффективной налоговой политики в развитых странах и странах БРИКС. Обоснована целесообразность исследования налогового стимулирования инвестиционно-инновационного развития промышленных предприятий с позиций эволюционного подхода с учетом закономерностей изменения правил и норм поведения хозяйствующих субъектов в пространстве и времени на долгосрочных интервалах времени. Усовершенствована эволюционная агентно-ориентированная модель инвестиционно-инновационного развития экономики для описания инерционного сценария деятельности промышленных предприятий Украины.